Penetapan Awal Bulan Qamariyah dalam Perspektif Maqāṣid Al-shari’ah - Ahmad Fauzan (Jurnal Hukum Islam, 2018)
Determining the first day of Qamariah months (Islamic calendar), particularly Ramadhan, Syawal, and Dzulhijjah, is deemed to be an interesting issue since the difference in time comes to the surface. This difference raises a debate among the government, Islamic mass organizations, and other parties almost every year in Indonesia. For instance, the difference in determining the first day of Syawal occurred in the era of New Order following the existence of Hisab and Rukyat Agency (BHR) in 1985, 1992, 1993, and 1998. The similar difference took place again in 2002, 2006, 2007, 2010, and 2011. The present study reveals that the tendency of this issue is caused by the height of hilal (the crescent moon) and the approach in determining the first day of Qamariah months. Maqasid al-shariah (sharia goals) promoted by Jasser Audah with several methods, namely: nature cognition, interrelated hierarchy, wholeness, openness, multi- dimensionality, and purposefulness, propose problem-solving in determining the first day of these months. This study highlights that the government has been less assertive in stipulating the time that should be followed by Indonesian Muslims regarding this difference. The government, the representation of imam (leader), is obliged to facilitate and support the implementation of worship in its totality, enhance unity in diversity to minimize a number of conflicts, and realize the common good by demonstrating the renewal of the National Institute of Aeronautics and Space (LAPAN) criteria (maslaḥat 'āmmah).